PERUNTUKAN UNDANG-UNDANG AURAT DAN PAKAIAN SOPAN MENURUT BIDANG KUASA MAJLIS PERBANDARAN KOTA BHARU BANDAR RAYA ISLAM: SATU HURAIAN - Abdullah, Mohd Azhar; Abdullah, Raihanah (Jurnal Syariah, 2010)
Aurat issue continues to be in turmoil not only in the west, in fact also in record in Muslims countries. This conflict often cause tragedy involving physical, mental and emotion that challenging faith and intelligence. Therefore, implementation of covering the aurat does not neglected from various challenges either external or internal. In Malaysia covering the aurat is not the main policy in country’s administration. Federal government action which gives choice on the enforcement of covering aurat, cause an ununiformity of aurat law in this country. Since 1992, Kelantan State Government is very committed in utilising the choice given by the federal gorvernment with more comprehentive method through Kota Bharu Municipal Councel-Islamic City (MPKB-BRI) law. In accordance with that, this writing surveys on how far the implementation of covering the aurat in business premises from historical background, jurisdiction, interpretation, sources and enforcement level. Research data are gathered through library research, especially from Islamic sources and law. Meanwhile the collected data from the field (secondary sources) obtained through the materials published by the MPKB-BRI. It is also reinforced by interviews of individuals who are directly involved.